Chitin Nanofiber Transparent Paper for Flexible Green Electronics. Issue 26 (4th May 2016) - Jin, Jungho; Lee, Daewon; Im, Hyeon‐Gyun; Han, Yun Cheol; Jeong, Eun Gyo; Rolandi, Marco; Choi, Kyung Cheol; Bae, Byeong‐Soo
Abstract : A transparent paper made of chitin nanofibers (ChNF) is introduced and its utilization as a substrate for flexible organic light‐emitting diodes is demonstrated. Given its promising macroscopic properties, biofriendly characteristics, and availability of the raw material, the utilization of the ChNF transparent paper as a structural platform for flexible green electronics is envisaged.